1991
DOI: 10.1002/j.1460-2075.1991.tb07669.x
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast mRNA 3′ end processing requires a nuclear-encoded RNA-binding protein.

Abstract: The protein coding regions of plastid mRNAs in higher plants are generally flanked by 3′ inverted repeat sequences. In spinach chloroplast mRNAs, these inverted repeat sequences can fold into stem‐loop structures and serve as signals for the correct processing of the mature mRNA 3′ ends. The inverted repeat sequences are also required to stabilize 5′ upstream mRNA segments, and interact with chloroplast protein in vitro. To dissect the molecular components involved in chloroplast mRNA 3′ end processing and sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
177
2

Year Published

1991
1991
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 181 publications
(184 citation statements)
references
References 25 publications
5
177
2
Order By: Relevance
“…All this has been taken as evidence that cpRNPs have no distinct binding sites on RNAs but rather associate nonspecifically with any ribosome-free RNA in the chloroplast (17). Specific members of the cpRNP family were implied in vitro in 3Ј-end processing of chloroplast mRNAs (19,20), in general mRNA stability (12), and in RNA editing (7). Only CP29A from Arabidopsis has been analyzed genetically (21).…”
mentioning
confidence: 99%
“…All this has been taken as evidence that cpRNPs have no distinct binding sites on RNAs but rather associate nonspecifically with any ribosome-free RNA in the chloroplast (17). Specific members of the cpRNP family were implied in vitro in 3Ј-end processing of chloroplast mRNAs (19,20), in general mRNA stability (12), and in RNA editing (7). Only CP29A from Arabidopsis has been analyzed genetically (21).…”
mentioning
confidence: 99%
“…These defects suggest that the normal Hcf5 gene function is involved in both the processing and the stability of selected chloroplast transcripts. Because these processes have been shown to be mediated in vitro by proteins interacting with the 3' end of the mRNA (Schuster and Gruissem, 1991;Hayes et al, 1996), RNA blots from hcf5 and normal siblings were probed with Arabidopsis genes for two of these proteins, 28RNP (Schuster and Gruissem, 1991;S. Abrahamson, personal communication) and 33RBP (Cheng et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…The lowered levels of the vbcL transcript could be an indirect effect of a decrease in translation, because it has been shown that in spinach this mRNA is highly sensitive to changes in chloroplast translation and processing (Klaff and Gruissem, 1991;Schuster and Gruissem, 1991 (Barkan, 1993). It h a s been suggested that this message, b u t not other chloroplast messages, was destabilized when not associated with ribosomes (Barkan, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that inverted repeats present at the 3' untranslated end of proteincoding transcription units may play a role as processing signals. They have been shown to be involved in mRNA processing and binding of plastid proteins in vitro (28,31).…”
Section: Discussionmentioning
confidence: 99%
“…Posttranscriptional processing (28,31) and/or translational arrest (6,16) are the most probable targets of specific gene expression control in plastids. The nature of the differential factors (and their mechanisms of action) that determine the phenotypic properties of each particular plastid population remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%